Exploring spirituality with older people: (1) rich experiences - Lepherd, Laurence (Journal of religion, spirituality & aging, 2020)
With an increasing aging population worldwide, there is a need for greater focus on the spirituality of older people, to better support them and lead them to an enhancement of their inner peace. This pilot research used a qualitative approach (with semi-structured interviews) in exploring spirituality with older people in residential aged care to understand more about the factors related to a sense of personal belief and connection that helped them in their daily lives. The research involved developing a rigorous exploratory process. The twenty-five (25) participants provided information about their rich experiences and their connections in four dimensions: (1) people, (2) creativity, (3) something bigger or higher than themselves and (4) their own inner being.